New mortgage designs for an inflationary environment : proceedings of a conference held at Cambridge, Massachusetts, January, 1975 - Modigliani, Franco; Lessard, Donald R.; Federal Reserve Bank of Boston (Boston: Federal Reserve Bank of Boston, 1975)
A collection of papers on 'New Mortgage Designs for Stable Housing in an inflationary Environment" presented at a conference at MIT in January 1975.
Cover title: New mortgage designs for stable housing in an inflationary environment. Sponsored by the Federal Reserve Bank of Boston, U.S. Dept. of Housing and Urban Development, and Federal Home Loan Bank Board.
Includes bibliographical references
oif 21/02/2019
Ref.
Keywords: Mortgages; Housing--Finance